(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The article examines the legal issues of artificial intelligence, highlighting the development and potential in various applications of the law. the opportunities and advantages appear to outweigh the risks and dangers. This is why one does not entirely agree with the EU Commission’s proposal to regulate AI. In general, with digital, it is more appropriate to have an animal legislation, which privileges the promotion of the activity rather than a complex regulation which accentuates limits and sanctions. The article closes with a focus on privacy and AI.